English Pre-Service Teachers' Knowledge of Linguistics in Indonesia - Cahya Komara; Widi Sriyanto (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2019)
This research studied the English pre-service teachers’ knowledge about linguistics in one of private university in Indonesia. By using the open-ended and close-ended questioners as it is fit with quantitative study, this research attempted to figure out the capacity of the English pre-service teachers in dealing with linguistics theory or understanding that is essential for them in giving full description or portrayal about English linguistics for teaching pupils at school. This research involved 100 respondents within 2 main focuses on micro-linguistics studies; 1) the morphology theory and understanding, 2) the phonology theory and understanding. The result showed there was a fact that English pre-service teachers had limit or paucity of linguistics understanding that can support them with better explanation and knowledge for teaching their future pupils.